Diagnosis of Primary Hyperventilation Syndrome by Polysomnography: A Report of Two Cases. Issue 3 (3rd June 1996) - Sheth, Tarang N; Kesten, Steven
Abstract : Two cases of primary hyperventilation syndrome misdiagnosed as asthma are reported. Polysomnography was used to diagnose the syndrome and to confirm the psychogenic etiology of the patients' symptoms.